(untitled) (Current Horticulture, 2024)
The field cum laboratory study was carried out to find out the effect of plant elicitors on papaya (Carica papaya L.) cv. Red Lady, during November, 2015 to October, 2017 at Horticultural Research Station, Anantharajupeta, Kadapa district, Andhra Pradesh. The application of salicylic acid twice (at 45 and 120 DAT) @ 150 ppm (T9) recorded significantly highest plant height (257.58 cm) at 210 DAT, which was at a par with T8(S.A @ 100 ppm at 45 DAT and 120 DAT) (225.08 cm and 34.21 cm). T9 (SA @ 150 ppm at 45 and 120 DAT) recorded significantly highest fruit weight (1.06 kg), fruit length (18.33 cm), fruit girth (43.02 cm). The values for all these parameters were found to be at par with T8 and T7, whereas lowest values was recorded with T13 (control), i.e. fruit weight (0.84 kg), fruit length (16.20 cm), fruit girth (33.35 cm). Significantly highest number of fruits/plant (60.37) was observed in T8 which was found to be at par with T9 (59.29) and T7 (57.94). Weight of fruits/plant (kg), yield/plot (kg) and yield/hectare (tonnes) were highest in T9 (49.78 kg, 552.42 kg and 116.06 tonnes/ha) which was at par with T8 (47.17 kg, 546.59 kg and 114.83 tonnes/ha). The lowest values in this regard were recorded in control (T13) (25.20 kg, 370.57 kg and 77.85 tonnes/ha).